A Ghost Textbook on the History of Medicine: A Case Study of the Legacy of a Stalinist Scholarly Canon. Issue 3 (2nd July 2020) - Zatravkin, Sergey; Vishlenkova, Elena
Abstract: Utilizing the minutes of preparations of a manuscript textbook on the history of medicine (1948-1953), the authors reconstruct how it was decided to depict the history of world and Russian medicine; in so doing sacralizing the Soviet state and wildly overstating its care for the health of Soviet people. The archival documents allowed the authors of the article to show how the aspirations and interests of the medical elite in the sacralization of their own role encouraged historians of medicine to develop not a scientific, but an epic version of the past and to repress other versions through political accusations and condemnation of colleagues. The textbook, which had been created and discussed for a long time in the 1940s, was never published. Nevertheless, the authors' reconstruction of its aborted conception made it possible to reveal its enduring formulations in later Soviet and even present-day textbooks, and enduring capacity to shape a Soviet style historical imagination in doctors.